Analysis of Equation of State for Carbon Nanotubes - Jeewan Chandra; Pooja Kapri Bhatt; Kuldeep Kholiya (Journal of Nanotechnology)
Compression behavior of carbon nanotube bundles and individual carbon nanotubes within the bundle has been studied by using the Suzuki, Shanker, and usual Tait formulations. It is found that the Suzuki formulation is not capable of explaining the compression behavior of nanomaterials. Shanker formulation slightly improves the results obtained by the Suzuki formulation, but only usual Tait’s equation (UTE) of state gives results in agreement to the experimental data. The present study reveals that the product of bulk modules and the coefficient of volume thermal expansion remain constant for carbon nanotubes. It has also been found that the individual carbon nanotubes are less compressible than bundles of carbon nanotubes.